Multiple-breath inert gas washout and spirometry versus structural lung disease in cystic fibrosis - Gustafsson, P M; De Jong, P A; Tiddens, H A W M; Lindblad, A (Thorax, 2008)
Background: A sensitive and valid non-invasive marker of early cystic fibrosis (CF) lung disease is sought. The lung clearance index (LCI) from multiple-breath washout (MBW) is known to detect abnormal lung function more readily than spirometry in children and teenagers with CF, but its relationship to structural lung abnormalities is unknown. A study was undertaken to determine the agreements between LCI and spirometry, respectively, with structural lung disease as measured by high-resolution computed tomography (HRCT) in children and teenagers with CF. Methods: A retrospective study was performed in 44 consecutive patients with CF aged 5–19 years (mean 12 years). At an annual check-up inspiratory and expiratory HRCT scans, LCI and spirometric parameters (forced expiratory volume in 1 s (FEV1) and maximal expiratory flow when 75% of forced vital capacity was expired (FEF75)) were recorded. Abnormal structure was defined as a composite HRCT score of >5%, the presence of bronchiectasis or air trapping >30%. Abnormal lung function was defined as LCI above the predicted mean +1.96 residual standard deviations (RSD), or FEV1 or FEF75 below the predicted mean −1.96 RSD. Sensitivity/specificity assessments and correlation analyses were done. Results: The sensitivity to detect abnormal lung structure was 85–94% for LCI, 19–26% for FEV1 and 62–75% for FEF75. Specificity was 43–65% for LCI, 89–100% for FEV1 and 75–88% for FEF75. LCI correlated better with HRCT scores (Rs +0.85) than FEV1 (−0.62) or FEF75 (−0.66). Conclusions: LCI is a more sensitive indicator than FEV1 or FEF75 for detecting structural lung disease in CF, and a normal LCI almost excludes HRCT abnormalities. The finding of an abnormal LCI in some patients with normal HRCT scans suggests that LCI may be even more sensitive than HRCT scanning for detecting lung involvement in CF.